PENGARUH KESADARAN MEMBAYAR PAJAK, PERSEPSI WAJIB PAJAK DALAM PELAKSANAAN SANKSI DENDA, SPPT, DAN PEMERIKSAAN PAJAK TERHADAP KEBERHASILAN PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DI KECAMATAN WANASARI KABUPATEN BREBES - Muttaqin, Ibnu; Anggra, Eva (PERMANA, 2018)
Ibnu Mustofa 4314500030 influence of awareness of paying taxes, perception of tax payers in the implementation of financial penalties, SPPT (Tax Payable Notification) and tax audit of the success of land tax revenues and rural and urban buildings in Wanasari District, Brebes Regency. Faculty of Economics and Business, Pancasakti University Tegal 2018. The purpose of this study is to find out whether awareness of paying taxes, the perception of tax payers in the implementation of financial penalties, SPPT (Taxable Income Tax Notification) and tax audit affect both simultaneously and partially on the success of land tax revenue and rural and urban buildings in Wanasari District, Brebes Regency. Population in this research is tax payer of earth and rural and urban building in District Wanasari Brebes Regency in year 2017 as many as 62,065. The sample is calculated using the Slovin formula, so that it gets a sample of 100 respondents. Data collection method uses a questionnaire. The analysis used is multiple linear regression analysis. The test results show that 1) Awareness of paying taxes, tax payer perception in the implementation of financial penalties, SPPT (Tax Notification Letters) and tax inspection simultaneously affect the success of tax revenue earth and rural and urban buildings in District Wanasari Brebes. 2) Awareness of paying taxes affect the success of tax revenue earth and rural and urban buildings in District Wanasari Brebes District. 3) Tax payer's perception in the implementation of financial penalties, SPPT (Tax Notification Letters) and tax audit have no effect on the success of tax revenue of earth and rural and urban building in Wanasari Sub-district of Brebes Regency.Keywords: Awareness of paying taxes, perceptions of taxpayers in the implementation of financial penalties, SPPT (Tax Return Letters), tax audit and the success of tax revenue earth and rural and urban buildings.